Migration Dynamics and New Trends in European (In)Security Crises, Challenges and Opportunities - IOV, Claudia Anamaria (Presa Universitară Clujeană, 2022)
In the 21st Century, migration-security relationship in Europe, in the context of globalization, takes on new dimensions with ample reverberations on the societal, economic, demographic, political, military and social fields. The refugee crisis, East-West/South-North chaotic migration, regional interethnic disputes, the “special operation” from Ukraine, became top priorities on the European security agenda. In this context, the volume brings to the fore, through a multidisciplinary analysis, the “complicated” relationship between migration and (in)security with a special focus on the integration process of migrants and refugees and the image of “ the other” (alterity). The book is part of a constructivist approach with a dynamic perspective on the political, social, economic, military and societal field, where the actors and the system structure are interconnected.